Pertumbuhan dan Hasil Kedelai di Lahan Rawa Lebak dengan Aplikasi Pupuk Hayati dan Kimia - ,, Endriani; Ghulamahdi, Munif; Sulistyono, dan Eko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Soybean (Glycine max L. Merrill) demand is high in Indonesia, however national production is low, therefore improving productivity is important. The research was aimed to determine the effect of application of biofertilizer containing N- fixing and P- solubilizing bacteria on the growth and production of soybean in lowland swamp. The experiment was conducted at Labuhan Ratu VI Village, District of Labuhan Ratu, East Lampung Regency from September to December 2014. The experiment was arranged in factorial randomized block design with three replications. N and P fertilizers were applied in four levels. Doses of N were 0, 11.25, 22.50, 33.75 kg ha-1, doses of P were 0, 36, 72, 108 P2O5 kg ha-1, in combination with and without biofertilizer application. The results showed that interaction between biofertilizer and N significantly affected number of branches and number of leaves at maximum vegetative phase. The influence of three types of fertilizer had no significant effect on the productivity of soybean in lowland swamp with soil pH of 7.0 and medium soil fertility. It is recommended to apply Biofertilizer + 11,25 kg N ha-1 + 36 kg P2O5 ha-1 to obtain high soybean production in lowland swamp area.Keywords: nitrogen, phosphate, productivity, soil fertility